The Golden and Silver Flowers – The Tributary Flowers: from a Symbol of Friendship to a Representation of Authority - Honghengseng, Kriangkrai (Journal of Thai Studies, 2023)
When discussing tributary offerings that appeared in historical records in the tributary state period, many may think of “golden and silver flowers or trees”, despite the fact that there were other kinds of the tributes that the tributary states offered to Siam, such as produce, local products, weapons and other economically valuable objects. It can be said that golden and silver flowers were construed as a symbol or a representation of political unevenness between the superior and the inferior states. Nevertheless, golden and silver flowers were more significant than being only a tribute – they became items of worship to religious objects and places, symbolizing becoming a Buddhist. They were later a gift or a tribute to felicitate the birth of a prince or princess, symbolizing the growth of the tree. They were also used for the sake of showing gratitude or royalty to the monarchy and for bartering commodity between countries. Finally, they were used in accolades or aggrandizement of the nobility or the investiture of a royal title. They also influenced Thai royal-court performing arts and literature.